2021
DOI: 10.3390/met11020192
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Corrosion Properties of Ti-to-Zr Dissimilar Alloy Joints Brazed with a Zr-Ti-Cu-Ni Amorphous Filler Alloy

Abstract: Titanium and Zircaloy-4 dissimilar alloys were brazed with a zirconium-titanium-copper-nickel amorphous filler alloy, and the resulting joint structures as well as their corrosion properties were examined. The microstructure of the brazed joints was investigated according to brazing holding time at 850 °C, and the corrosion property was analyzed by potentiodynamic polarization. During brazing, joints were produced by diffusion-induced isothermal solidification of the molten filler alloy. At a relatively brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Compared with crystalline Ti-based alloys, amorphous titanium alloys exhibit higher mechanical properties [ 10 , 11 ], low elastic modulus, excellent biocompatibility and high corrosion resistance. With the development of titanium-based amorphous alloys, Ti-rich bulk glassy alloys were found in rapidly solidified Ti-Cu-Al [ 12 , 13 ], Ti-Cu-Ni (Co) [ 14 , 15 , 16 ], Ti-Cu-Zr-Ni [ 17 , 18 ], Ti-Cu-Co-Al-Zr [ 19 ] and Ti-Cu-Ni-Sn (Si) [ 20 , 21 ] systems to date. Since 1988, many alloys with high glass-forming ability and capable of being formed into bulk metallic glasses (BMG) have been discovered more and more, for example, in multicomponent Mg-, La-, Zr-, Fe- and Pd-based metals in the alloy system.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with crystalline Ti-based alloys, amorphous titanium alloys exhibit higher mechanical properties [ 10 , 11 ], low elastic modulus, excellent biocompatibility and high corrosion resistance. With the development of titanium-based amorphous alloys, Ti-rich bulk glassy alloys were found in rapidly solidified Ti-Cu-Al [ 12 , 13 ], Ti-Cu-Ni (Co) [ 14 , 15 , 16 ], Ti-Cu-Zr-Ni [ 17 , 18 ], Ti-Cu-Co-Al-Zr [ 19 ] and Ti-Cu-Ni-Sn (Si) [ 20 , 21 ] systems to date. Since 1988, many alloys with high glass-forming ability and capable of being formed into bulk metallic glasses (BMG) have been discovered more and more, for example, in multicomponent Mg-, La-, Zr-, Fe- and Pd-based metals in the alloy system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adding Zr to Ti provides good biocompatibility, high mechanical strengths, and excellent corrosion resistance [12]. In this regard, many researchers have report the rule of Zr in improving the corrosion resistance as well as the biocompatibility of Ti [11][12][13][14][15]. As an example, Akimoto et al [13] studied the effect of different additions of Zr; namely, 30%, 50%, and 70%, on the corrosion of Ti in lactic acid containing sodium chloride solution and found that 30% Zr and at a Zr < 50% offer an ideal level of corrosion resistance for clinical applications.…”
Section: Introductionmentioning
confidence: 99%